An analysis of earnings manipulation by firms in South Africa (2000-2016) an empirical report - Mudzimba, Darlington (My University, 2018)
This report investigated, incidences of earnings manipulation by firms listed on the Johannesburg Stock Exchange (JSE). The empirical analysis was based on three forensic accounting models namely modified Jones model, Beneish M-score and the Altman model. South Africa has not been immune from such financials scandals, with notable examples being Unifer, Leisurenet, Saambou, Fidentia. Sharemax, Randgold, First Strut (FirstTech Group), African Bank and most recently Steinhoff. The report also investigates whether or not market participants levy any penalty to firms that engage in earnings manipulation. . For the purpose of this analysis the report employs the Capital Asset Pricing Model The approach of this report is that any firm year flagged by at least two of the model, will be classified as having engaged in earnings manipulation. Empirical analysis reveal that on the whole 6.76% firm years in the sample engaged in earnings manipulation. In particular financial years 2013, 2014 & 2015 exhibited high incidences of firms flagged for earnings management. The report concludes, (after controlling for determinants of cost of capital in accounting and finance literature that have not been subject of this report) that there is no evidence to suggest that JSE stock exchange investors demand a higher expected required return from earnings manipulator firms relative to non-manipulators.
Submitted in fulfillment of the Requirements for the Degree of Masters of Management in finance and investments